ePortfolio Faculty Development Workshop: Using a Sociocultural Medicine Curriculum as an Example - Monica Lypson; Paula Ross; Rachel Perlman; Jennifer Christner (Association of American Medical Colleges, 2013)
Abstract This resource provides comprehensive guidelines for conducting a multistage faculty development program for the implementation of an ePortfolio. This resource provides faculty with the opportunity to develop their assessment skills and experience hands-on training for providing quality feedback through mentored reflection. This resource includes moderator instructions, practice exercises, sample student essays, sample evaluation forms, sample scoring criteria, a didactic PowerPoint, a learner packet, and supplemental curriculum content materials. Faculty members found the workshops to be effective in all domains. Specifically, they reported that the workshops gave them the tools they needed to stimulate reflection and evaluate the students' assignments, both of which were primary duties of the faculty. We found it useful for the faculty to work with actual student materials. Even with new curriculum initiatives, we worked to have senior students write an essay or provide an example for faculty to react to. In addition, having faculty use all the same materials allowed for appropriate bench-marking and evaluation processes.